Genetic differences in the accumulation of mineral elements in seeds of tropical soybeans Glycine max (L.) Merrill - Spehar, Carlos Roberto (Pesquisa Agropecuaria Brasileira, 1995)
The soybean is a major crop in the agricultural systems of the Brazilian Cerrados (Savannahs), whose soils are acidic, devoid of nutrients and need to be amended before they are cultivated. However, below the ploughed layer, there is scarcity of nutrients and toxic aluminium. These limit root growth, causing nutritional unbalance and drought stress. The mineral element content in the seeds may be negatively affected, with consequences to humans and livestock. The present work aimed to identify genetic differences of mineral element accumulation in the seeds of soybeans by a 9 x 9 diallel cross among adapted varieties, grown in high and in low-Al areas. The Covariance (Wr) - Variance (Vr) relationship indicated that the additive-dominance model explained the genetic differences in this germplasm for Ca, Mg, Al and Mn. For the elements P, K, Fe, Zn, Cu, Mo, Na and Ti, the genetic effects seemed more complex. The level of mineral elements was affected by Al and pH but did not compromise food quality. Additional studies are suggested to further clarify the genetics of mineral element accumulation in soybean seeds.